Crucial amino acids identified in Δ12 fatty acid desaturases related to linoleic acid production in Perilla frutescens - Wu, Zhenke; Li, Mingkai; Liang, Xiqin; Wang, Jun; Wang, Guoli; Shen, Qi; An, Tianyue (Frontiers in Plant Science, 2024)
Perilla oil from the medicinal crop Perilla frutescens possess a wide range of biological activities and is generally used as an edible oil in many countries. The molecular basis for its formation is of particular relevance to perilla and its breeders. Here in the present study, four PfFAD2 genes were identified in different perilla cultivars, PF40 and PF70, with distinct oil content levels, respectively. Their function was characterized in engineered yeast strain, and among them, PfFAD2-1 PF40 , PfFAD2-1 PF70 had no LA biosynthesis ability, while PfFAD2-2 PF40 in cultivar with high oil content levels possessed higher catalytic activity than PfFAD2-2 PF70 . Key amino acid residues responsible for the enhanced catalytic activity of PfFAD2-2 PF40 was identified as residue R221 through sequence alignment, molecular docking, and site-directed mutation studies. Moreover, another four amino acid residues influencing PfFAD2 catalytic activity were discovered through random mutation analysis. This study lays a theoretical foundation for the genetic improvement of high-oil-content perilla cultivars and the biosynthesis of LA and its derivatives.